Polycystic ovarian syndrome: a modern overview - S O Dubrovina (IP Berlin A.V., 2016)
Polycystic ovarian syndrome (PCOS) is one of the most common metabolic and reproductive disorders among women of reproductive age. Women suffering from PCOS have a whole complex of symptoms associated with menstrual dysfunction and androgen excess, which significantly impacts their quality of life. They may be at increased risk of multiple morbidities, including obesity, insulin resistance, type II diabetes mellitus, endometrial cancer, and psychological disorders. This review summarizes guidelines to diagnosis of PCOS, stress on the various aspects of treatment and screening recommendations currently used in the management of this condition.